Effects of Autotomy on Haemolymph Profile and Mineral Composition in Mud Crab (Scylla serrata) at Pre and Post- Moulting Cycle - Yusnaini, Yusnaini; Yanti, Esri; Sabilu, Kadir; Fekri, Latifa; Nur, Indriyani (Universitas Negeri Semarang, 2025)
Soft-shell crab is a valuable product variant in aquaculture, with moulting being a critical phase for its production. Physiological indicators such as haemolymph profiles and mineral content in muscle tissue are essential for assessing crab health and moulting performance. This study aimed to evaluate the effect of autotomy treatment on the physiological condition of mud crab (Scylla serrata), focusing on haemolymph characteristics and mineral concentrations in muscle during the pre-moulting and post-moulting phases. The treatment involved inducing autotomy of walking legs and claws. Sampling was conducted at four distinct phases: pre-autotomy, 15 hours post-autotomy, at immediate post-moult stage, and two days post-moulting. The physiological parameters observed included Total Haemocyte Count (THC) and Differential Haemocyte Count (DHC), comprising hyaline, semi-granular, and granular cell types. Muscle mineral content was assessed by measuring calcium, sodium, and phosphorus concentrations. Results indicated that autotomy reduced THC and the proportion of hyaline cells, while granular cells increased during the post-moulting phase. Calcium, sodium, and phosphorus concentrations decreased shortly after autotomy, peaked during moulting, and declined again after moulting. These findings provide insight into the physiological responses of mud crabs to autotomy and offer practical reference points for enhancing moulting success and supporting soft-shell crab production in aquaculture systems.